Chapter Le Giudicarie e la val Vestino: i Lodron e i da Campo - Cagol, Franco (Reti Medievali E-Book, 2023)
In the 14th and 15th centuries, the rural lordships of the Lodrone and da Campo families asserted themselves in the geographically complex area of the Sarca valley, open to the territory of Brescia.